Postoperative human epididymis protein 4 predicts primary therapy outcome in advanced epithelial ovarian cancer - Tuulia Vallius; Johanna Hynninen; Annika Auranen; Jaakko Matomäki; Sinikka Oksa; Pia Roering; Seija Grènman (Tumor Biology)
Primary chemotherapy treatment response monitoring in advanced epithelial ovarian cancer (EOC) is currently based on CT-imaging and serum CA125 values. Serum HE4 profile during first line chemotherapy has not been previously studied. We evaluated the HE4 profile during first line chemotherapy after primary (PDS) and interval debulking surgery (IDS). In total, 49 FIGO stage III/IV EOC patients were included in the study. 22 patients underwent PDS and 27 patients neoadjuvant chemotherapy (NACT) followed by IDS. Serial HE4 and CA125 serum samples were taken during first line chemotherapy. The association of postoperative tumor markers to surgery outcome, primary therapy outcome and progression free survival (PFS) were determined. The lowest HE4 and CA125 values during chemotherapy were compared to primary therapy outcome and PFS. The postoperative HE4 was associated to residual tumor after surgery (p = 0.0001), primary therapy outcome (p = 0.004) and PFS (p = 0.03) in all patients (n = 40). The postoperative CA125 was associated to PFS after IDS (n = 26, p = 0.006), but not after PDS. In multivariate analysis with FIGO stage (III/IV), residual tumor (0/>0) and postoperative CA125, the postoperative HE4 was the only statistically significant prognostic variable predicting PFS. Both HE4 and CA125 nadir corresponded to primary therapy outcome (HE4 p < 0.0001, CA125 p < 0.0001) and PFS (HE4 p = 0.009, CA125 p < 0.0001). HE4 is a promising candidate for EOC response monitoring. In our study, the performance of HE4 in response monitoring of first line chemotherapy was comparable to that of CA125. Of the postoperative values, only HE4 was statistically significantly associated to primary therapy outcome.